Necessary characteristics for publication in nursing journals: scoping review protocol (Research, Society and Development, 2022)
Background: The characteristics present in a scientific article contribute to its being considered of quality and having greater chances of publication. Objective: To analyze the scientific evidence available in the literature on the characteristics necessary for the publication of scientific articles in nursing journals. Method: Scoping review protocol based on the Joanna Briggs Institute. It intends to answer the following question based on the Population-Concept-Context (PCC) strategy: What scientific evidence is available in the literature on the characteristics necessary for the publication of scientific articles in nursing journals? Studies that addressed the relevant characteristics in the writing of scientific articles in nursing journals, available in full, without temporal and/or language limitations, were included. Results: The description of the findings will occur in a descriptive way, through a table, in which will be the main results of each included study. Conclusion: Scientific writing as well as research execution criteria are determining factors for publication in journals with a higher impact factor.